Kualitas Layanan TPQ terhadap Karakter Islami Anak Pesisir melalui Kepercayaan Orang Tua - Muh Andi Sulaiman; Fenilinas Adi Artanto (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the influence of the quality of Al-Qur'an Education Park (TPQ) services, consisting of teacher competence and the learning environment, on the Islamic character of early childhood, with parental trust as a moderating variable. A quantitative approach using the Structural Equation Modeling (SEM) method was used. The study subjects were 110 parents of early childhood children who participated in TPQ activities in the coastal area of ​​Wiradesa District, Pekalongan Regency. The results showed that teacher competence had the most dominant influence on children's Islamic character, followed by the learning environment, which also had a significant influence. Parental trust did not have a direct effect on children's Islamic character, but had a significant moderating role. Parental trust was shown to strengthen the influence of the learning environment on Islamic character, but actually weakened the influence of teacher competence in the child's education process. This study confirms that the quality of TPQ plays an important role in the formation of children's Islamic character in coastal areas, but its effectiveness is influenced by the active involvement of parents. Therefore, synergy between TPQ and families is the main key in optimizing Islamic character education for early childhood.